2018
DOI: 10.1097/ogx.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid for Prevention and Treatment of Postpartum Hemorrhage: An Update on Management and Clinical Outcomes

Abstract: Importance Postpartum hemorrhage (PPH) remains a major cause of maternal mortality worldwide, occurring in both vaginal and cesarean deliveries. We have witnessed improvements in both prevention and treatment of PPH. Tranexamic acid (TXA) has been investigated as a potential adjunct therapy to uterotonics within this setting. Objective The aim of this article is to summarize existing recommendations on the use of TXA in obstetrics and review current dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
0
18
0
5
Order By: Relevance
“…There was no increase in the incidence of thrombosis in various clinical trials with oral tranexamic acid doses of up to 6000 mg. 24 Some preliminary in vitro studies of TA using thromboelastometry also showed that the administration of TA at greater than 10-fold therapeutic levels in blood from pregnant women before delivery does not increase the hypercoagulable profile. 25 Headache, nausea, menstrual irregularity and back pain are the most commonly reported side effects of TA. 16,23 Contraindications of TA include kidney dysfunction, cardiovascular or respiratory disease, malignancy, current anticoagulant therapy and history of thromboembolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…There was no increase in the incidence of thrombosis in various clinical trials with oral tranexamic acid doses of up to 6000 mg. 24 Some preliminary in vitro studies of TA using thromboelastometry also showed that the administration of TA at greater than 10-fold therapeutic levels in blood from pregnant women before delivery does not increase the hypercoagulable profile. 25 Headache, nausea, menstrual irregularity and back pain are the most commonly reported side effects of TA. 16,23 Contraindications of TA include kidney dysfunction, cardiovascular or respiratory disease, malignancy, current anticoagulant therapy and history of thromboembolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, recently there has been more focus on acute treatment of PPH with increased early use of tranexamic acid. Several studies have already shown and currently further studies are ongoing about the effective use of tranexamic acid as a first-line therapy or even prophylactic use for PPH [17,[26][27][28][29]. Other studies have indicated that the administration of carbetocin as well as oxytocin can effectively prevent PPH after vaginal delivery [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid is the drug of choice in patients within 3 h after the onset of hemorrhage. 3,33) Fluid therapy, blood transfusion, and antishock therapy should be initiated without delay while paying attention to vital signs. Circulatory maintenance is attempted by rapid administration of colloid solution and albumin solution until a blood transfusion can be administered.…”
Section: Seeking a Uterus-preserving Hemostatic Strategymentioning
confidence: 99%
“…1,2) Numerous trial-and-error approaches have been taken to secure effective hemostasis for difficult obstetrical uterine hemorrhage cases. 2) Various surgical hemostatic procedures including arterial ligation, supravaginal amputation of the uterus, and hysterectomy, in addition to procedures such as bimanual uterine compression, intrauterine tamponade, uterotonic therapy, administration of tranexamic acid, 3) and treatment of DIC, have been used. Along with the spread of interventional radiology (IVR) techniques in the field of obstetrics, hemostatic management using preventive hemostasis and embolization became feasible in the 1990s, leading to a major advancement in the management of uterine hemorrhage.…”
Section: Introductionmentioning
confidence: 99%